Managing Policy Mess - Roe, Emery (Governance in Turbulent Times, 2016)
What are the conditions for political development and decay, and the l ikelihood of sustained political order? What are the limits of establi shed rule as we know it? How much stress can systems tackle before the y reach some kind of limit? How do governments tackle enduring ambigui ty and uncertainty in their systems and environments? These are some o f the big questions of our time. Governance in turbulent times may ser ve as a stress-test of well-known ways of governing in the 21st centur y. Governance in Turbulent Times discusses this pertinent challenge an d suggests how governments and organizations cope with and live with t urbulence. The book explores how organizations and institutions respon d to precipitous, conflicting, and novel-in short, turbulent-governanc e challenges. This book is a comprehensive and ground-breaking endeavo r to understand how governance systems respond to turbulent challenges , and how turbulent times provide excellent opportunities to investiga te the sustainability of governance systems. The book illustrates how politics, administrative scale and complexity, uncertainty, and time c onstraints can collide to produce turbulence. Building on prior work i n organization theory and political science, we argue that turbulence refers to four properties related to the interaction of demands for ac tion: variability, consistency, expectation, and unpredictability. Tur bulence occurs where the interaction of demands is experienced as high ly variable, inconsistent, unexpected, and/or unpredictable.
Keywords: Comparative Politics; International Relations; Political Process; Political science; Public Affairs & Administration